Systems Analysis Reveals Contraceptive-Induced Alteration of Cervicovaginal Gene Expression in a Randomized Trial - Balle, Christina; Gupta, Prachi M.; Tharp, Gregory K.; Nelson, Sydney A.; Konstantinus, Iyaloo N.; Lennard, Katie; Jaumdally, Shameem Z.; Happel, Anna-Ursula; Barnabas, Shaun L.; Gill, Katherine; Bekker, Linda-Gail; Passmore, Jo-Ann S.; et al. (Frontiers in Reproductive Health, 2022)
Hormonal contraceptives (HCs) are vital in managing the reproductive health of women. However, HC usage has been linked to perturbations in cervicovaginal immunity and increased risk of sexually transmitted infections. Here, we evaluated the impact of three HCs on the cervicovaginal environment using high-throughput transcriptomics. From 2015-2017, 130 adolescent females aged 15-19 years were enrolled into a sub-study of UChoose, a single-site open-label randomized, crossover trial (NCT02404038) and randomized to injectable norethisterone-enanthate (Net-En), combined oral contraceptives (COC) or etonorgesterol/ethinyl-estradiol-combined contraceptive vaginal ring (CCVR). Cervicovaginal samples were collected after 16 weeks of randomized HC use and analyzed by RNA-Seq, 16S rRNA gene sequencing and Luminex analysis. Participants in the CCVR arm had significant elevation of transcriptional networks driven by IL-6, IL-1 and NFKB, and lower expression of genes supporting epithelial barrier integrity. An integrated multivariate analysis demonstrated that networks of microbial dysbiosis and inflammation best discriminated the CCVR arm from the other contraceptive groups, while genes involved in epithelial cell differentiation were predictive of the Net-En and COC arms. Collectively, these data from a randomized trial represent the most comprehensive ‘omics analyses of the cervicovaginal response to HCs and provide important mechanistic guidelines for the provision of HCs in sub-Saharan Africa.